2023
DOI: 10.3390/bs13070587
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Turkey and Syria Earthquakes on University Students: Posttraumatic Stress Disorder Symptoms, Meaning in Life, and Social Support

Othman A. Alfuqaha,
Uday M. Al-masarwah,
Randa I. Farah
et al.

Abstract: (1) Background: Earthquakes are natural disasters that often result in significant loss of life and property. The objective of this study is to explore the frequency of symptoms associated with posttraumatic stress disorder (PTSD), levels of meaning in life (ML), and perceived social support (SS) among university students in the aftermath of the earthquake that occurred in Turkey and Syria in 2023. (2) Methods: This study utilizes a cross-sectional correlation design to achieve its objectives among 603 univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The implications of this finding are particularly significant for university students who have experienced traumatic events such as earthquakes, which can deeply disrupt their sense of meaning and purpose in life 1 . However, our study highlights gratitude as a potential protective factor that can enhance students’ perception of MIL even in adversity 7 .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The implications of this finding are particularly significant for university students who have experienced traumatic events such as earthquakes, which can deeply disrupt their sense of meaning and purpose in life 1 . However, our study highlights gratitude as a potential protective factor that can enhance students’ perception of MIL even in adversity 7 .…”
Section: Discussionmentioning
confidence: 97%
“…This finding emphasizes the importance of consistently fostering the practice of gratitude to harvest cumulative benefits over time. Given the ongoing challenges students face, particularly those affected by the trauma of earthquakes, cultivating these positive attributes becomes even more crucial in promoting their resilience and well-being amidst adversity 1 . The results highlight the potential of gratitude and LE as protective factors, which, when nurtured over time, may contribute to a greater sense of MIL, offering valuable implications for supporting students’ psychological growth and adjustment in the aftermath of the earthquake.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have highlighted the unique pressures that university students encounter, including academic demands, extreme stressors, financial constraints, and personal growth expectations [ 12 , 13 ]. Furthermore, it was observed that Jordanian university students exhibited pronounced signs and symptoms of PTSD following a crisis situation [ 14 ] as well as general population following the COVID-19 pandemic [ 15 ]. Given the significant impact of these stressors and crises on student well-being, validating a psychological resilience scale among Jordanian university students is of paramount importance to the wider Jordanian population.…”
Section: Introductionmentioning
confidence: 99%
“…PTSD usually occur after traumatic occurrences that exceed the range of common human experience (for example, domestic violence, rape, torture, warfare, accidents, human-made, and natural disasters) that affect the mind and behavior of the individual [ 10 , 11 ]. It is characterized by a typical symptom pattern of disturbing thought process, emotional numbness, attempts to avoid trauma-related cues, and physiological hyper-arousal [ 10 ].…”
Section: Introductionmentioning
confidence: 99%